Detection of Eutrophication In Benoa Bay - Bali - Yulianto Suteja; I Gusti Ngurah Putra Dirgayusa (Journal Omni-Akuatika, 2018)
Eutrophication is an increase of organic material caused by the increase of nutrients in aquatic ecosystem by human activities. One effect of eutrophication is Harmful Algae Blooms (HABs) that are very harmful to the environment and humans. The Purpose of this study were determine spatial distribution of nutrient based on total nitrogen (total N) and total phosphate (total P), ratio of total N, and trophic level in Bay Benoa. Nutrient measurements were using spectrophotometric method. The Spatial distribution of total N and P show a generally pattern concentration increases in waters near the mainland. The highest concentrations of total N and P were found in Loloan River estuary closed to the floating net cages (FNC). Ratio of total N showed generally that the waters in Benoa Bay were dominated by Nitrate. High ammonia concentration was found in all rivers and Loloan River estuary. Benoa Bay is mostly in Oligotrophic conditions based on total N, while eutrophic conditions were only found in the Loloan River estuary. Based on total P, Benoa Bay was generally in hypertrophic level.